Marketplace Entrepreneur Sorgum Menggunakan Klastering K Medoid - Saurina, Nia; Noerhartati, Endang; Revitriani, Marina (Universitas PGRI Kanjuruhan Malang, 2023)
Marketplace is a virtual market where the market is a meeting place for buyers and sellers to make transactions. Wijaya Kusuma University Surabaya has established an Entrepreneurship Sorghum Unit (UES) starting in 2009 and is collaborating with Sorghum Entrepreneurs in several areas in East Java. The objectives of this research are: (1) creating a marketplace for Sorghum Entrepreneurs who have joined UES, (2) Classifying using the K-Medoid method to group Sorghum Entrepreneurs based on the income that has been obtained by UES, (3) Conducting mapping based on clustering results so that UES can provide assistance to sorghum entrepreneurs. From the results of the questionnaire, obtained data on the level of desire for UES for each variable from 35 sorghum entrepreneurs as respondents. Quantitative data obtained is then entered and then proceed with the clustering stage. The data is divided into several clusters based on the type of sorghum, products sold and sales results. After that, the cluster performance calculation is carried out by calculating the k-fold value. analysis of the results of testing the effect of the k-fold value is the best percentage found in the k-fold value = 6 with an accuracy value of 34.597%.